Program Latihan Profesi (PLP) Dalam Meningkatkan Kemampuan Pedagogi Mahasiswa - Hidayatullah, Taufiq; Rosmilawati, Ila (Program Studi Pendidikan Luar Sekolah, 2025)
Abstract: The aim of this research is to combine theoretical knowledge learned in lectures with applications that can be found in the real world. This study applies a quantitative descriptive approach. We were placed at SPNF SKB Serang City for this Professional Training Program (PLP) activity. The department's PLP program assists with teaching activities, office administration, and archiving. This research uses learning implementation observation sheets and learning implementation plan (RPP) review sheets to obtain data. Students have overall